Sex difference in tDCS current mediated by changes in cortical anatomy: a study across young, middle and older adults - Bhattacharjee, Sagarika (2022)
The observed variability in the effects of transcranial direct current stimulation (tDCS) is influenced by the amount of current reaching the targeted region-of-interest (ROI). Age and sex might affect current density at target ROI due to their impact on cortical anatomy. The present tDCS simulation study investigates the effects of cortical anatomical parameters (volumes, dimension, and torque) on simulated tDCS current density in healthy young, middle-aged, and older males and females.